Effect of humidity on electrical conductivity of pristine and nanoparticle-loaded hydrogel nanomembranes - Khan, Musammir; Schuster, Swen; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2015)
We studied here the effect of humidity on the electrical conductivity of pristine and nanoparticle-loaded hydrogel nanomembranes. The membranes were fabricated by the thermally activated cross-linking of amine- and epoxy-terminated, star-branched poly(ethylene glycol) (PEG) oligomers. The resistance of the pristine membrane changed by ∼5.5 orders of magnitude upon relative humidity (RH) variation from 0% to 100%, which is an unprecedented response for homogeneous materials. The dependence of the resistance on the moisture uptake into the membrane could be coarsely described by an exponential function. The loading of the membranes with gold and silver nanoparticles (NPs) resulted in a noticeable improvement of their conductance at low RH but in a small improvement or even a negative effect on the conductance at high RH. Both pristine and NP-loaded PEG hydrogel membranes have significant potential as highly sensitive elements in humidity sensors and moisture-responsive nanoelectronic devices.